Strong and ductile poly (lactic acid) achieved by carbon dioxide treatment at room temperature. (October 2019) - Chai, Jialong; Wang, Guilong; Li, Bo; Wan, Gengping; Zhang, Lei; Zhao, Guoqun
Graphical abstract: SYNOPSIS: A green method to strengthen and toughen PLA by carbon dioxide (CO2 ) treatment at room temperature. Highlights: Strong and ductile PLA was prepared by simple CO2 treatment at room temperature. CO2 treatment induced numerous nanoscale rod-like crystallites. CO2 treatment led to significantly improved strength, rigidness, and toughness. CO2 treatment dramatically increased the Vicat softening temperature of PLA. Abstract: Poly (lactic acid) (PLA) is a biodegradable and biocompatible polymer derived from renewable resources that demonstrates an immense potential in replacing fossil-based polymers. Nevertheless, its inherent brittleness and poor thermal resistance significantly restrict its further applications. Developing an environmentally friendly and cost-effective method for strengthening and toughening PLA without sacrificing its other functional properties remains a challenge. In this study, we report a novel method to reinforce PLA by carbon dioxide (CO2 ) treatment at room temperature. Remarkably, CO2 treatment led to simultaneously enhanced strength, toughness, ductility and thermal resistance. Under 3.5 MPa CO2 treatment, PLA demonstrated the best mechanical performance with tensile strength, ductility, and impact toughness enhanced by 25%, 1214%, and 134%, respectively. Moreover, the Vicat softening temperature was significantly enhanced from 55.8 °C to 155.3 °C. Wide angle X-ray diffraction, Fourier transform infrared spectroscopy, and differential scanning calorimetry elucidate the strengthening and toughening mechanism to be CO2 -induced crystallization. The small-angle laser scattering and scanning electron microscope demonstrate the formation of numerous nanorod crystallites, which are responsible for coincidentally enhancing the strength, toughness, and thermal resistance. Thus, CO2 treatment at room temperature provides a green and effective method to provide high-performance PLA products that have immense potential in biomedical, automotive, and other structural applications.